Translanguaging for Higher Education Learning: Perspectives From International Students in Thailand - Daron Benjamin Loo; Anita Sundaresan; Leong Jin Jee (TRANSBAHASA, 2022)
International student mobility is a common phenomenon observed globally, especially in higher education settings where English is used as the main medium of instruction. In such settings, international students may find themselves using English along with their first language for social or academic purposes. This study examines international students’ perspectives towards translanguaging in a university setting. With a mixed-methods approach, an anonymous online questionnaire and open-ended survey were distributed to international students. A total of 74 international students comprising 16 nationalities completed the survey. From the quantitative data, the students indicated a generally positive perspective towards translanguaging, especially to become more confident in English use and to relate better with other international students. Further quantitative analysis indicated that the perceptions differed significantly across years of study. The qualitative data provided further insights regarding translanguaging, namely the suitability of using a shared language in a formal learning context, such as in the classroom. All in all, this study was able to provide further insights into international students’ perspectives towards translanguaging.